Pemberian Makanan Bergizi Seimbang terhadap Kejadian Stunting pada Balita - Sri Hartini; Sulistyaningsih Sulistyaningsih (Journal of Telenursing (JOTING), 2022)
This study aims to determine how providing balanced nutritious food affects the incidence of stunting in toddlers. The method used is scoping review with the PRISMA-ScR framework and scoping review questions with the PICO framework. Article searches were conducted through the Pubmed, ScienceDirect and Wiley databases with Critical Appraisal based on The Joanna Briggs Institute (JBI). The results showed that three main themes were found, namely: 1) knowledge, affecting the growth and development of children, the higher the mother's education, the better her level of knowledge; 2) economic status, which influences the incidence of stunting because if the economic status is good, then the family is not lacking in terms of food; 3) good feeding practices, is an indicator to assess the optimal fulfillment of a child's nutritional needs. In conclusion, providing nutritious food with balanced nutrition for children is the main factor that significantly influences the incidence of stunting in toddlers. Keywords: Toddlers, Nutrition, Stunting, Balanced Nutrition